Autologous Hematopoietic Stem Cell Transplantation for Liver Transplant Recipients With Recurrent Primary Sclerosing Cholangitis: A Pilot Study. Issue 3 (25th May 2021) - Chruscinski, Andrzej; Juvet, Stephen; Moshkelgosha, Sajad; Renner, Eberhard; Lilly, Leslie; Selzner, Nazia; Bredeson, Christopher; Grant, David; Adeyi, Oyedele; Fischer, Sandra; Demetris, Anthony J.; Zhang, Jianhua; et al.
Abstract : Background: Primary sclerosing cholangitis (PSC) is an indication for liver transplantation, but recurrence after liver transplantation is associated with poor outcomes often requiring repeat transplantation. We investigated whether autologous hematopoietic stem cell transplantation (aHSCT) could be used to stop progression of recurrent PSC and promote operational tolerance. Methods: Twelve patients with recurrent PSC were fully evaluated and 5 were selected for aHSCT. Autologous hematopoietic stem cells were collected, purified by CD34 immunomagnetic selection, and cryopreserved. Immunoablation using busulfan, cyclophosphamide, and rabbit antithymocyte globulin was followed by aHSCT. The primary endpoint of the study was the establishment of operational tolerance defined as lack of biochemical, histologic, and clinical evidence of rejection while off immunosuppression at 2 y post-aHSCT. Results: Two of the 5 patients achieved operational tolerance with no clinical or histologic evidence of PSC progression or allorejection. A third patient developed sinusoidal obstruction syndrome following aHSCT requiring repeat liver transplantation but has no evidence of PSC recurrence while on sirolimus monotherapy now >3 y after aHSCT. A fourth patient was weaned off immunosuppression but died 212 d after aHSCT from pericardial constriction. A fifth patient died from multiorgan failure. Immunosuppression-free allograft acceptance was associated with deletion of T-cell clones, loss of autoantibodies, and increases in regulatory T cells, transitional B cells, and programmed cell death protein-1 expressing CD8 + T cells in the 2 long-term survivors. Conclusions: Although operational tolerance occurred following aHSCT, the high morbidity and mortality observed render this specific protocol unsuitable for clinical adoption. Abstract :